(3GddeYI GdeSei aj Md GdSHYIs - (3GdQjTj, GdgfOj, TgGH GdOjf, CMeO Hf ZdGe Gddg Hf CMeO Hf eMeO Gdche, J (B836(3g`s ((3ESMGb eSYhO GdQgGhj Hf eMehOs)
(3ChdgG (B:s
(3jbhd GdYHO GdabjQ Edi Gddg JYGdi CMeO Hf CMeO Gdche GdQjTj GdeDbJ HLGeY GdeDjO(B... (3GdMeO ddg dGPj LYd GdYde TeSGs
(3BNQgG (B:s
(3aef hbY dg ZjQ Pdc hGKbG HUMJg adjUdMg hjYJeO Ydi Pdc aef Yai hCUdM CLQg Ydi Gddg JYGdi(B. (3bO Je GdcJGH(B...s
(3JHUQI GdeDda (B:s
(3aj agQSI cGTa GdZWGA(B: (3GdchGes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: (3L(B1(3, U(B192s
(3GdCYdGe(B: (3L(B1(3, U(B192s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdadc hGdJfLje hGdejbGJs